Treatment patterns and outcomes for patients with locally advanced basal cell carcinoma before availability of Hedgehog pathway inhibitors: a retrospective chart review - Lear, John T.; Leverkus, Martin (European journal of dermatology, 2017)
Background: Understanding the molecular basis of basal cell carcinoma (BCC) has led to development of Hedgehog pathway inhibitors (HPIs) for patients with advanced forms of BCC (aBCC). A practical definition of aBCC as a distinct disease entity is unavailable, and epidemiological information is limited. Objectives: To conduct the RONNIE study to describe characteristics, treatment patterns, and outcomes of patients with aBCC during the period preceding HPI introduction, as well as results from patients with locally advanced BCC (laBCC). Materials & methods: A retrospective chart review was conducted using data from adult patients with a new diagnosis of laBCC between 1st January 2005 and 31st December 2010. The study period was 1st January 2005 to 31st December 2011 to allow for inclusion of at least 12 months of follow-up information for all patients. Results: Treatment data were available for 106/117 patients. Radiation and excisional surgery were the most common first-line treatment options (43.4% and 23.5% of patients, respectively). Patients typically received multiple subsequent treatments; no apparent trend or pattern was observed. Complete visual response, partial visual response, and stable disease were obtained in 51.9%, 25.9%, and 11.1% of patients, respectively, after first-line surgery, and in 53.7%, 22.0%, and 9.8%, respectively, after first-line radiation. Median progression-free survival after first-line treatment was 32.1 months. Median overall survival was 78.8 months. Conclusions: These data represent a baseline for laBCC before HPIs became part of the treatment algorithm. The observed heterogeneity of treatment patterns highlights the lack of an established standard treatment for laBCC before HPIs were available.
Gesehen am 14.11.2018